Aktuální trendy ve vývoji webových aplikací - Jasný, Vojtěch; Brabec, Tomáš; Špánek, Roman; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2007)
The thesis is divided between two main topics: the first are trends in web application development on the client-side. Described are AJAX and COMET techniques, JSON format for data interchange, tools usable to debug Javascript applications and three Javascript libraries. Important part of client-side development are forms, which are far from ideal in their current state. Hence description of XForms and Web Forms 2.0 and their comparison is included. The second topic is server-side development. First the most used technologies used today are evaluated. Further, several frameworks are described and compared on a set of criteria. Python, Ruby and Java languages are represented.
Vedoucí práce: Tomáš Brabec
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2007
Rok obhajoby 2007
Keywords: informatika [obor bakal. práce]; bakalářské práce; bachelor's theses